Polydopamine-Based Nanocarriers for Photosensitizer Delivery - Xiong, Yuxuan; Xu, Zushun; Li, Zifu (Frontiers in Chemistry, 2019)
Photodynamic therapy (PDT) has emerged as a non-invasive modality for treating tumors while photosensitizer (PS) plays an indispensable role in PDT. Nevertheless, free photosensitizers (PSs) are limited by their low light stability, rapid blood clearance and poor water-solubility. Constructing a nanocarrier delivering PSs is an appealing and potential way to solve these issues. As a melanin-like biopolymer, polydopamine (PDA) is widely utilized in biomedical applications (drug delivery, tissue engineering and cancer therapy) for its prominent properties, including favorable biocompatibility, easy preparation and versatile functionality. PDA based nanocarriers are thus leveraged to overcome the inherent shortcomings of free PSs. In this Mini Review, we will firstly present an overview on the recent developments of PDA nanocarriers delivering PSs. Then, we introduce three distinctive strategies developed to combine PSs with PDA nanocarriers. The advantages and disadvantages of each strategy will be discussed. Finally, the current challenges and future opportunities of PDA-based PS nanocarriers will also be addressed.